Novel iron (II) complexes of 1, 5-diaza-3, 7-diphosphacyclooctanes. (27th May 2019) - Dayanova, Irina R.; Nikolaeva, Yulia A.; Kharyushin, Ivan V.; Strelnik, Igor D.; Khabibullin, Roman M.; Balueva, Anna S.; Musina, Elvira I.; Karasik, Andrey A.
Abstract: New cationic octahedral bis-ligand iron (II) complexes of 1, 5-diaza-3, 7-diphosphacyclooctanes were synthesized as mixtures of two cis-isomers with different mutual arrangement of Fe–P-bonds and co-ligands which may be separated by a fractional crystallization. Graphical Abstract: UF0001